Minimally invasive plate osteosynthesis (MIPO) combined with distraction osteogenesis in the treatment of bone defects: A new technique of bone transport: A report of two cases - Apivatthakakul T. (2014)
This study reports two cases of fracture of the femur with segmental bone loss that were treated by a new technique of bone transport. A minimally invasive plate osteosynthesis (MIPO) bridge from the proximal to distal femur served as a fixation system. A separate Wagner distraction apparatus was used for distraction osteogenesis. After the transport segment docked with the bone fragment, it was fixed to the plate by a percutaneous screw fixation. The Wagner lengthening device was then removed. The total time of external fixation was significantly reduced. A satisfactorily functional result and bone segment regeneration was achieved. The external fixation index was 0.31 and 0.37 month/cm, and the limb length discrepancy was 0.9 and 1.2cm. The advantages of this technique include a decrease in the duration of external fixation, protection against refracture and earlier rehabilitation. © 2002 Elsevier Science Ltd. All rights reserved.